DESIGNING LIFE AND CAREER SKILLS-INTEGRATED SPEAKING SYLLABUSES FOR ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Muhammad Eka Zuwanda; Sri Sumarni; Siti Drivoka Sulistyaningrum (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
Life and Career Skills (LCS) are already considered to be the essential skills to get equipped by the next generation in anticipating and facing complex challenges in life and work environment in the 21st century era. In preparing skillful and compatible next-generation, the educational institution has a responsibility to evolve fast by addressing the 21st century-skills into educational systems such as curriculum or syllabuses. In other hands, speaking skill has become a skill which is significant to master in utilizing language properly in various social context so that it has a function in understanding, composing, or interacting expressions, ideas, and opinion. Therefore, this study aims to design Life and Career Skills-integrated speaking syllabuses for ELESP by conducting a need analysis of Life and Career Skills towards nineteen syllabuses for speaking courses from six universities in Indonesia. The analysis is carried out by employing LCS indicators which are developed from some frameworks or theories of LCS proposed by the National Association of Colleges and Employers (NACE) (2019), Binkley et al. (2012), and Partnership for 21st Century Skills (P21) (2009). The design of this study is Design and Development Research (DDR) proposed by Ellis & Levi (2010); and Gall & Borg (2003) and qualitative descriptive as a research method used in this study. The findings reveal that Life and Career Skills have been integrated implicitly and explicitly into speaking syllabuses which appear mostly in syllabus components such as Course Description, Learning Objectives, Learning Outcomes, Materials, Teaching Methods, Learning Media, Assessment/Evaluation, and Course Policy. Oral/Written Communication and Critical Thinking competencies are the main LCS-indicators which are highly addressed in the existing speaking syllabuses. This study sets for the procedure of LCS integration and the design of Life and Career Skills-integrated speaking syllabuses; Speaking for General Purposes, Speaking for Professional Purposes, and Speaking for Academic Purposes. A skill-based syllabus is referred to design the proposed syllabuses.